Building Babies 2012
DOI: 10.1007/978-1-4614-4060-4_16
|View full text |Cite
|
Sign up to set email alerts
|

When Dads Help: Male Behavioral Care During Primate Infant Development

Abstract: In contrast to birds, male mammals rarely help to raise the offspring. Of all mammals, only among rodents, carnivores, and primates, males are sometimes intensively engaged in providing infant care (Kleiman and Malcolm 1981). Male caretaking of infants has long been recognized in nonhuman primates (Itani 1959). Given that infant care behavior can have a positive effect on the infant’s development, growth, well-being, or survival, why are male mammals not more frequently involved in “building babies”? We begin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 131 publications
1
17
0
Order By: Relevance
“…80–90%) from very soon after birth, and infants only transfer to the mother for brief periods usually around the time of active nursing bouts. This pattern has been documented for every group of owl monkey and titis we have studied in the field (owl monkeys N = 15, titis N = 5: Fernandez‐Duque, Di Fiore, & de Luna, ; Huck & Fernandez‐Duque, ; Juárez, Rotundo, & Fernandez‐Duque, ; Rotundo, Fernandez‐Duque, & Giménez, ; Spence‐Aizenberg, Di Fiore, & Fernandez‐Duque, ). Moreover, we found that adult owl monkey males share food with infants more frequently than do mothers (Wolovich, Perea‐Rodriguez, & Fernandez‐Duque, ) and are also the first source of support when an infant faces a challenging situation (e.g., crossing a canopy gap, Rotundo et al, ).…”
Section: Our Research Program On “Monogamy” In Wild Platyrrhinessupporting
confidence: 55%
See 2 more Smart Citations
“…80–90%) from very soon after birth, and infants only transfer to the mother for brief periods usually around the time of active nursing bouts. This pattern has been documented for every group of owl monkey and titis we have studied in the field (owl monkeys N = 15, titis N = 5: Fernandez‐Duque, Di Fiore, & de Luna, ; Huck & Fernandez‐Duque, ; Juárez, Rotundo, & Fernandez‐Duque, ; Rotundo, Fernandez‐Duque, & Giménez, ; Spence‐Aizenberg, Di Fiore, & Fernandez‐Duque, ). Moreover, we found that adult owl monkey males share food with infants more frequently than do mothers (Wolovich, Perea‐Rodriguez, & Fernandez‐Duque, ) and are also the first source of support when an infant faces a challenging situation (e.g., crossing a canopy gap, Rotundo et al, ).…”
Section: Our Research Program On “Monogamy” In Wild Platyrrhinessupporting
confidence: 55%
“…For our study taxa, we quantified “paternal care” as defined by Opie et al (), that is, by calculating the males' percent contribution to infant carrying as a value from the infant's perspective, where infant care by all caregivers adds up to 100%. By this criterion, in wild Azara's owl monkeys ( A. azarae azarae ), males carry infants at least 75% of the time (Huck & Fernandez‐Duque, ), and for a different subspecies ( A. a. boliviensis ), a value of 92% has been estimated in an 8‐month study of captive individuals (Jantschke, Welker, & Klaiber‐Schuh, ). In our study of two wild red titis groups ( P. discolor ), males are clearly the main carriers of immature infants, responsible for 98% of carrying time (Spence‐Aizenberg et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral data were collected following research protocols (available upon request), that are utilized for comparative purposes in studies of owl monkeys in Argentina (Fernandez‐Duque & Huck, ; Fernandez‐Duque & van der Heide, ; Huck & Fernandez‐Duque, , ), as well as studies of titis ( C. discolor ) and sakis ( Pithecia aequatorialis ) in Yasuní National Park in Ecuador (Porter, Grote, Isbell, Fernandez‐Duque, & Di Fiore, ; Spence‐Aizenberg et al, ; Van Belle, Fernandez‐Duque, & Di Fiore, ). In brief, each focal sample consisted of a 20 min period during which all behavioral events (e.g., movements, social interactions, foraging) were recorded and the behavioral state of the focal individual (resting, foraging, moving, socializing, other, or out of view) was recorded every 2 min (i.e., focal sampling point).…”
Section: Methodsmentioning
confidence: 99%
“…While cooperative breeding is highly derived and unusual in primates, other, more facultative forms of AMC are common [17]. AMC is widespread in primates [8,19,52,53], and occurs at much greater frequency in the Order compared with other mammalian Orders (e.g., [17,[54][55][56]), suggesting early or repeated and strong pressure for it to have evolved [9]. Comparative study of species with less derived versions of AMC can inform on the selective pressures and mechanisms that allowed cooperative breeding to evolve in our own species.…”
Section: Introductionmentioning
confidence: 99%